Synergy management pitfalls in mergers and acquisitions. Issue 7 (17th August 2015) - Fiorentino, Raffaele; Garzella, Stefano
Abstract : Purpose: – The purpose of this paper is to advance a conceptual comprehensive framework to analyze synergy management pitfalls in mergers and acquisitions (M & As). The framework highlights the main dimensions of synergy management, the most relevant synergy pitfalls and the ways to overcome them. Design/methodology/approach: – A greater recognition of synergy management literature in M & As is developed. A framework is provided integrating the compatible elements of previous broad areas of research and the main findings of studies on several topics related to synergy. Findings: – Prior literature has suggested that synergy is an important motivation of M & As, has tended to be overestimated and has been difficult to achieve. Specifically, there are three relevant synergy pitfalls: the "mirage, " a tendency to overestimate synergy potential, the "gravity hill, " the underestimation of the difficulties in synergy realization and "amnesia, " a dangerous lack of attention to the realization of synergy. An effective synergy management requires an analysis of five dimensions: the steps of the M & A process, the several values of synergy, the forbidding effects of poor synergy management, the potential causes of synergy inflation and the selection of solutions to synergy pitfalls. Practical implications: – The comprehensive framework suggests insights and guidelines to help managers to overcome pitfalls in synergy management. Managers will learn the following lessons: "when" pitfalls should embrace synergy management; "where" pitfalls may occur; "why" pitfalls may occur; "what" consequences can result in a value of "realized synergy" lower than the "expected synergy"; and "how" actions, tools and behaviors can overcome hidden dangers in synergy management. Originality/value: – The study changes the focus from a single, generic synergy trap to three more analytical, useful synergy pitfalls: the mirage, the gravity hill and the amnesia. By shedding light on synergy management pitfalls, this paper enriches M & A literature and enhance practical solutions to reduce pitfalls in synergy decision making.